Legal Political Study on Translation of Human Rights in the Indigenous Peoples in Dharmasraya West Sumatera District - Andiki, Febri; ALW, Lita Tyesta (Universitas Islam Negeri Walisongo Semarang, 2020)
The national land law structure in force in Indonesia does not mention and does not prohibit the sale and purchase of customary land rights. The fact in customary law has conditions that must be met regarding the transfer of the sale of customary land rights. If it does not meet the requirements, then buying and selling rights to customary land is said to be a deviation regarding the objectives contained in the customary order. Formulation of the first problem, why the legality of buying and selling rights over customary land of the Malay tribe in Dharmasraya Regency, West Sumatra Province. Second, what is the form of transfer of customary land rights according to customary law and national land law in Dharmasraya Regency and what kind of government legal policy is capable of providing protection to customary community rights relating to customary land rights? This paper is the result of research using the Socio Legal Research method that uses primary data and secondary data is a source of questions with the collection techniques carried out by observation and interviews equipped with literature studies and analyzed descriptively prescriptive. The results of the study found a deviation regarding the substance of the transfer of title to the Malay customary land. One of the factors is the undeniable development of the age related to economic survival without thinking about the common rights inherent in customary land. The conclusion is that the customary land is a common right of the customary law community. The meaning of collective rights here is not owned by individuals, ‘ninik mamak’ or customary leaders only. Therefore, the sale and purchase of customary land rights must be returned in accordance with customary law norms attached to the customary law community itself. So that the existence of customary land is maintained in the days to come and is not eroded by time. The future legal politics of the government pays attention to the existence of customary land and recognizes the customary community's customary land to be poured in the form of an authentic deed and poured in the form of a Regency / City Regional Regulation in terms of the transfer of customary rights to other parties, especially investors.